The anatomy of design : uncovering the influences and inspirations in modern graphic design - Heller, Steven (Rockport, 2011)
"Anatomy of Design dissects fifty examples of graphic design piece by piece, revealing an array of influences and inspirations. These pieces represent contemporary artifacts that are well conceived, finely crafted, and filled with hidden treasures. Some are overtly complex. Others are so simple that it is hard to believe there's a storehouse of inspiration hidden underneath. The selections include all kinds of design work including posters, packages, and more. Each exhibit is selected for its ubiquity, thematic import, and aesthetic significance, and every page shows how great work is derived from various inspirational and physical sources, some well-known, some unknown. Each design is presented on a gate-fold showing the featured design and and other works that share the key influences with extended captions explaining the whys and wherefores."--Publisher's website.